2019
DOI: 10.1108/jstp-12-2018-0295
|View full text |Cite
|
Sign up to set email alerts
|

Managing customer relationships in emerging markets

Abstract: Purpose The purpose of this paper is to study the impact of relationship comfort and relationship proneness on the ability of service firms to build and maintain customer relationships in emerging markets (EMs). Design/methodology/approach A field-survey was conducted with retail-banking customers in India (n=300) using a structured self-administered questionnaire with well-established scales. Findings Relationship comfort positively affects key relationship marketing (RM) constructs (e.g. customer satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 88 publications
(102 reference statements)
1
8
0
Order By: Relevance
“…However, Shen et al (2019) [43] state that trust is one of the most important aspects, along with a contract, for creating a long-term relationship. To create a relationship in the tourism industry, customer relationship management or CRM is employed as an effective strategy to increase sales and profit [12,44].…”
Section: Brand Management In the Crisismentioning
confidence: 99%
See 1 more Smart Citation
“…However, Shen et al (2019) [43] state that trust is one of the most important aspects, along with a contract, for creating a long-term relationship. To create a relationship in the tourism industry, customer relationship management or CRM is employed as an effective strategy to increase sales and profit [12,44].…”
Section: Brand Management In the Crisismentioning
confidence: 99%
“…Brands tend to be significantly affected during a crisis if not properly managed, and it often requires significant resources to ensure that a brand survives during a period of adversity. Iglesias et al (2020) [11] employed the concept of corporate branding to manage risk because it can increase customers' trust and reduce the perceived risk [12]. Recently, Wang et al (2020) [13] demonstrated that the brand image could reduce tourists' risk perception from a crisis.…”
Section: Introductionmentioning
confidence: 99%
“…A high level of customer interaction indicates a robust link between customers and the firm (Islam and Rahman, 2016). Customers tend to build relationships that support their beliefs, feelings and behavior and thus minimize psychological rigidity in maintaining relationships (Gaur et al , 2019). For this reason, understanding the role of interaction intensity in building customer–firm relationships will provide a practical guideline for bankers who seek to strengthen their relationships with customers.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Moreover, Adjei and Clark (2010) suggest that a customer’s proneness to engage in a deep firm relationship exerts a positive moderating effect on the relationship quality–loyalty interface in the apparel context. Moreover, while Gaur et al (2019) suggest that banking customers’ relationship proneness strengthens the effect of relationship comfort on customer commitment and loyalty, Menidjel and Bilgihan (2021) show that relationship proneness positively moderates the impact of customer-perceived relationship investments on their experienced relationship value.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…That is, more (vs less) relationship-prone customers are expected to exhibit a greater tendency to stay with a firm (vs switch), thus, supporting its relationship marketing efforts (Odekerken-Schröder et al , 2003). However, despite its pertinence, the role of customer relationship proneness in influencing their engagement and switching intention remains nebulous (Gaur et al , 2019), as, therefore, also explored in this research. Overall, our analyses derive enhanced acumen of the theoretical interface of customer variety-seeking, engagement, switching intention and relationship proneness, which – despite elevated managerial relevance – remains tenuous to date.…”
Section: Introductionmentioning
confidence: 99%